Mirabegron as effective as oxybutynin for ureteral stent symptoms - Jaworski,Paulo (2021)
SUMMARY OBJECTIVE: Ureteral stents usually cause pain and lower urinary tract discomfort. This study aimed to compare the effect of mirabegron with oxybutynin in relieving ureteral stent-related symptoms over time. METHODS: A prospective, longitudinal, randomized, single-blinded study was conducted. Patients who had a ureteral stent inserted after urolithiasis treatment were classified into two groups and received either oxybutynin 5 mg/day (Group O) or mirabegron 50 mg/day (Group M). The Ureteral Stent Symptoms Questionnaire (USSQ) was applied on the 3rd, 6th, and 15th postoperative days. Group domain scores were compared, and a mixed linear model was used to better assess score differences. RESULTS: Ureteral Stent Symptoms Questionnaire scores were similar in both groups during all three postoperative days (p>0.05). A longitudinal analysis showed that global quality of life and general health improved over time, independently of the use of any of the medications (p<0.05), while urinary symptoms and body pain scores were lower over time in participants receiving oxybutynin. CONCLUSION: Both mirabegron and oxybutynin are equivalent in relieving ureteral stent symptoms. Moreover, some stent symptoms seem to decrease over time despite the use of medication.